ECONOMIC FEASIBILITY STUDY FOR THE PROJECT OF CULTURED BARLEY PRODUCTION WITH HYDROPONIC METHOD - Diana M . Kaleel; E . H . Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The objective of this research is to know the economic feasibility of hydroponics technology by estimating the expected demand for green forage for the years 2021-2031 as well as Identify and analyze project data and information in a way that helps the investor make the appropriate investment decision in addition to preparing a detailed technical preliminary study for the cultivar barley project focusing on the commercial and financing aspects and the criteria that take into account the risks and uncertainties . that indicating the economic feasibility of the project to produce green forage using hydroponics technology. Cultured barley as a product falls within the blue ocean strategy. Accordingly, the research recommends the necessity of implementing such projects that save land, water, and fertilizers and provide green forage throughout the year. The government should provide financial support for the supply and establishment of these projects because they require large capital, and livestock owners need support because the demand for forage is a request to implement an indicative program to introduce the advantages of hydroponics and green forage to breeders to increase the demand for it.